Genome-wide identification of nitrate transporter genes from Spirodela polyrhiza and characterization of SpNRT1.1 function in plant development - Lv, Mengli; Dong, Tiantian; Wang, Jin; Zuo, Kaijing (Frontiers in Plant Science, 2022)
Nitrate transporter (NRT) genes that participate in nitrate transport and distribution are indispensable for plant growth, development, and stress tolerance. Spirodela polyrhiza has the smallest genome among monocotyledon plants, and it has strong nitrate absorbance and phytoremediation abilities. However, the evolutionary history, expression patterns, and functions of the NRT gene family in S. polyrhiza are not well understood. Here, we identified 29 NRT members in the S. polyrhiza genome. Gene structure and phylogeny analyses showed that S. polyrhiza nitrate transporter (SpNRTs) genes were divided into eight clades without gene expansion compared with that in Arabidopsis. Transcriptomic analysis showed that SpNRT genes have spatiotemporal expression patterns and respond to abiotic stress. Functional analysis revealed that in S. polyrhiza, SpNRT1.1 expression was strongly induced by treatment with nitrate and ammonium. Overexpression of SpNRT1.1 significantly repressed primary root length, and the number and total length of lateral roots. This was more pronounced in high ammonium concentration medium. Overexpressed SpNRT1.1 in Arabidopsis significantly improved biomass and delayed flowering time, indicating that the nitrate transport ability of SpNRT1.1 differs from AtNRT1.1. To conclude, our results provide valuable information about the evolution of the NRT family in higher plants and the function of SpNRT1.1.